The influence of treated oleo-chemical wastewater applications on the metal speciation forms in soils - Żak, Sławomir; Rauckyte-Żak, Terese; Laurinavičius, Alfredas (Journal of Environmental Engineering and Landscape Management, 2013)
This paper presents a developed method of pretreating wastewaters coming from small-tonnage oleo-chemical production and also the research results on the variability of concentrations of heavy metals (Cd, Cr, Cu, Ni, Pb, Zn) in the soil irrigated and fertilized with wastewater from this production. The processing wastewater pretreatment was carried out at two stages. The first stage eliminated fatty substances by using dispersed air flotation aided with hydrogen peroxide as an oxidizer. The second stage included coagulation and chemical precipitation with milk of lime, flocculation, final dissolved air flotation (DAF), and also oxidation with hydrogen peroxide. Field experiments, the aim of which was to compare variability levels for speciation fractions of heavy metals, were carried out according to Tessier’s method for four years. The study revealed that the average concentrations of the given metals fractions in soil samples where raw wastewaters were directed did not significantly change during the experiment, which clearly justifies the need for their physical–chemical pretreatment and further agro-utilization without the risk of soil environment degradation. The successive decrease of exchangeable fraction, the increase in the content of the fraction bound with carbonate forms, and stability of the fraction bound with hydrated iron and manganese oxides as well as organic and residual fractions were found in soil samples treated with pretreated wastewaters.